Legacy Data Confound Genomics Studies - Anderson-Trocmé, Luke; Farouni, Rick; Bourgey, Mathieu; Kamatani, Yoichiro; Higasa, Koichiro; Seo, Jeong-Sun; Kim, Changhoon; Matsuda, Fumihiko; Gravel, Simon (Molecular biology and evolution, 2020)
Recent reports have identified differences in the mutational spectra across human populations. Although some of these reports have been replicated in other cohorts, most have been reported only in the 1000 Genomes Project (1kGP) data. While investigating an intriguing putative population stratification within the Japanese population, we identified a previously unreported batch effect leading to spurious mutation calls in the 1kGP data and to the apparent population stratification. Because the 1kGP data are used extensively, we find that the batch effects also lead to incorrect imputation by leading imputation servers and a small number of suspicious GWAS associations. Lower quality data from the early phases of the 1kGP thus continue to contaminate modern studies in hidden ways. It may be time to retire or upgrade such legacy sequencing data.